Pengaruh Kadar Filler Abu Sawit (Ukuran Direduksi) Dan Temperatur Pencampuran Terhadap Morfologi Dan Sifat Komposit Polipropilen/karet Alam - Melda Helena S; Bahruddin Bahruddin; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Morphology and properties of composites PP/NR is influenced by the condition of the rawmaterial mixing process between the phase and compatibility. The purpose of this study was toinvestigated the effect of blend content filler fly ash and mixing temperature on morphology andmechanical properties of polypropylene (PP)/NR composite. Filler size is reduced by MechanicalMilling process until the filler size ≤ 700 nm. Variation of blend kontent fly ash (reducted particlesize) 30, 40, 50 and 60 phr were studied in order to determine the optimum content of fly ash(reducted particle size). The rubber compound  has been made by two roll mill at ambienttemperature and 20 rpm rotor speed. Dynamic vulcanization was done on internal mixer at variousmixing temperature 170 oC, 175 oC, 180 oC , and 185 oC. Rotor speed on internal mixer at 60 rpm.The mechanical properties was done by Universal Testing Machine (UTM) and the morphologywas examined by Scanning Electron Microscopy (SEM). The optimum result was found at thecontent of fly ash (reducted particle size) 40 phr and the optimum temperature  was 175oC. The bestmechanical properties was given on tensile strength 4,3 MPa, elongation at break 28,1 % and modulus elastic 104,2 MPa.Keywords: ash oil, composites PP / NR, mechanical properties, natural rubber,  polypropylen.